The risks to Australia from emerging and exotic arboviruses - Mackenzie, John; Van Den Hurk, A. (Cambridge Publishing, 2018)
The recent pandemic spread of mosquito-borne arboviruses across multiple continents, as exemplified by West Nile (WNV)1,, chikungunya (CHIKV)2, and Zika (ZIKV)3, viruses, together with the continuing disease burden of epidemic dengue viruses (DENVs)1, multiple importations of yellow fever virus (YFV) into populous areas of Asia4, and the potential threat of some other, possibly unknown, emerging arboviral threat, constitute a wake-up call for governments to strengthen surveillance programmes and enhance research into mosquito-transmitted diseases5–7. Rift Valley fever8 (RVFV) and Japanese encephalitis1,9 (JEV) viruses are also important examples of threats to human and/or livestock health. Australia is vulnerable to these arboviral diseases, with risk of importation and outbreak potential varying between viruses10. The risk of exotic arboviral diseases establishing transmission cycles in Australia is dependent on the availability of competent vectors and suitable vertebrate hosts. Therefore, knowledge of the vector competence of Australian mosquito species for exotic arboviruses, potential for the introduction and establishment of exotic vector species, and suitability of vertebrate hosts, are essential components of understanding and mitigating these arboviral threats.